Childhood obesity: can the scale weigh popularity?. Issue 10 (24th August 2019) - Kornilaki, Ekaterina N.; Cheng, Helen
ABSTRACT: In hypothetical playmate preference tasks, obese figures are rarely picked up as friends. This study aims to observe what happens in real life and examine the relationship between body-size and social status in children. Four-hundred and fourteen children aged 5, 7 and 9 years were given a sociometric test. The Body Mass Index (BMI) of each child was calculated. Children were classified as average, popular or with a negative social status. A negative association between body-size and popularity was found. Popular children had the lowest mean BMI, while neglected and rejected children had the highest. Not a single obese child was found to be popular while overweight children had more chances to be popular with increasing age. The findings suggest that obesity is a risk factor for children's social development as early as preschool age.